Charcoal Versus Manganese Mineral Wad and the Geochronology of the Kimmswick Clovis Site. (3rd April 2017) - Haynes, C. Vance; Stanford, Dennis; Johnson, Donald L.
ABSTRACT: Hydrated manganese oxide, known as mineral wad, is sometimes mistaken for charcoal, as US National Museum geologist W. H. Holmes and archaeologist Gerald Fowke did in 1902. Here we discuss the Kimmswick Clovis site as an example and provide recent radiocarbon results pertinent to Mississippi Valley geochronology.